2022
DOI: 10.1002/slct.202203005
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters as a Fluorescent Probe for the Sensitive Determination of Morin and Sensing of Temperature

Abstract: The fluorescence detection has attracted extensive attentions because of its selective and sensitive determining characteristics for a series of analytes. In this detection system, a fluorescence method was first developed for the analysis of morin (MR) based on gold nanoclusters, which was prepared using tryptophan as the stabilizer and reducing agent. The assynthesized gold nanoclusters (Trp-Au NCs) showed maximum excitation wavelength and emission wavelength at 368 and 449 nm, respectively. When MR was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Based on these requirements, in the last 10 years, several production processes have emerged, where only one smaller or larger molecule like proteins [ 8 , 9 ], peptides [ 10 ] and simple amino acids [ 11 , 12 , 13 ] are used for the reduction of metal ions (e.g., [AuCl 4 ] − , Ag + or Cu 2+ ), which in addition play a dominant role in the stabilization and functionalization of the metallic surface as well. In the case of amino acids, several articles can be found for tryptophan (Trp) [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], tyrosine (Tyr) [ 21 , 22 ], histidine (His) [ 12 , 13 , 23 ], arginine (Arg) [ 24 ], or amino acids containing S donors like cysteine (Cys) or methionine (Met) [ 11 , 13 ]. Among these amino acids for Trp, it was confirmed that Au- [ 12 , 15 , 16 , 18 , 20 ], Ag- [ 14 , 19 ], and Cu-based [ 18 ] NCs can also be produced via a direct reduction of the metal ions with Trp without the application of any other agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these requirements, in the last 10 years, several production processes have emerged, where only one smaller or larger molecule like proteins [ 8 , 9 ], peptides [ 10 ] and simple amino acids [ 11 , 12 , 13 ] are used for the reduction of metal ions (e.g., [AuCl 4 ] − , Ag + or Cu 2+ ), which in addition play a dominant role in the stabilization and functionalization of the metallic surface as well. In the case of amino acids, several articles can be found for tryptophan (Trp) [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], tyrosine (Tyr) [ 21 , 22 ], histidine (His) [ 12 , 13 , 23 ], arginine (Arg) [ 24 ], or amino acids containing S donors like cysteine (Cys) or methionine (Met) [ 11 , 13 ]. Among these amino acids for Trp, it was confirmed that Au- [ 12 , 15 , 16 , 18 , 20 ], Ag- [ 14 , 19 ], and Cu-based [ 18 ] NCs can also be produced via a direct reduction of the metal ions with Trp without the application of any other agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of amino acids, several articles can be found for tryptophan (Trp) [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], tyrosine (Tyr) [ 21 , 22 ], histidine (His) [ 12 , 13 , 23 ], arginine (Arg) [ 24 ], or amino acids containing S donors like cysteine (Cys) or methionine (Met) [ 11 , 13 ]. Among these amino acids for Trp, it was confirmed that Au- [ 12 , 15 , 16 , 18 , 20 ], Ag- [ 14 , 19 ], and Cu-based [ 18 ] NCs can also be produced via a direct reduction of the metal ions with Trp without the application of any other agents. By comparing the experimental conditions optimized in these publications, it can be stated that predominantly the use of ligand excess (depending on the metal ions, these are in the range of a 2:1–20:0 molar ratio, 100–120 °C temperature, and basic conditions (pH = 11–12)) can be generally used to produce blue-emitting Trp-coated NCs.…”
Section: Introductionmentioning
confidence: 99%